8 - Recent Trends and Patterns of Gasoline Consumption in Nigeria - Yingigba Jaja, Chioma (Africa Development, 2021)
This article analyses recent trends and spatial patterns of gasoline consumption in Nigeria. In particular, it shows that the volume of gasoline consumption in the country fluctuates with changes in economic growth. The pattern of distribution of gasoline consumption indicates that the largest consumption centres are in the South-West and South-South geopolitical zones of the country, specifically Lagos, Oyo, Ogun, Edo, Rivers and Delta States. Other locations of high gasoline consumption are Kaduna, Kano, Imo states and Abuja (Federal Capital Territory). Compared with a previous study, the four additional centres identified are Ogun, Delta, Imo States and Abuja (FCT). Results of the multiple regression analysis show that the spatial variation in gasoline consumption is related to the number of gasoline-using vehicles newly registered and per capita income in the states. The study provides a framework for the development of meaningful policies for the reduction of transportation-related energy consumption.